Facing social exclusion: a facial EMG examination of the reaffiliative function of smiling. Issue 4 (19th May 2022) - Brandenburg, Joseph C.; Albohn, Daniel N.; Bernstein, Michael J.; Soto, Jose A.; Hess, Ursula; Adams, Reginald B.
ABSTRACT: Social exclusion influences how expressions are perceived and the tendency of the perceiver to mimic them. However, less is known about social exclusion's effect on one's own facial expressions. The aim of the present study was to identify the effects of social exclusion on Duchenne smiling behaviour, defined as activity of both zygomaticus major and the orbicularis oculi muscles. Utilising a within-subject's design, participants took part in the Cyberball Task in which they were both included and excluded while facial electromyography was measured. We found that during the active experience of social exclusion, participants showed greater orbicularis oculi activation when compared to the social inclusion condition. Further, we found that across both conditions, participants showed greater zygomaticus major muscle activation the longer they engaged in the Cyberball Task. Order of condition also mattered, with those who experienced social exclusion before social inclusion showing the greatest overall muscle activation. These results are consistent with an affiliative function of smiling, particularly as social exclusion engaged activation of muscles associated with a Duchenne smile.